The Influence of Work Climate, Work Culture, and Contract Commitment on Teacher Performance and Conflict Management in Islamic Elementary Schools: A Systematic Study - Erlina,; Gistituati, Nurhizrah; Anisah,; Al Kadri, Hanif (Journal of Learning Improvement and Lesson Study, 2024)
This study aims to systematically review the literature that discusses the influence of work climate, work culture, and commitment to contracts on teacher performance and conflict management in Islamic elementary schools. Using the Systematic Literature Review (SLR) approach, this article identifies research trends, theories used, and factors that contribute to improving teacher performance and conflict management in Islamic educational environments. This article is expected to provide practical recommendations for school administrators in creating a conducive and harmonious work environmen.